2022
DOI: 10.3892/ijo.2022.5406
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA 01614 hyperactivates WNT/β‑catenin signaling to promote pancreatic cancer progression by suppressing GSK‑3β

Abstract: Pancreatic cancer (PC) is a lethal type of cancer for which effective therapies are limited. Long non-coding RNAs (lncRNAs) represent a critical type of regulator category, mediating the tumorigenesis and development of various tumor types, including PC. However, the expression patterns and functions of numerous lncRNAs in PC remain poorly understood. In the present study, linc01614 was identified as a PC-related lncRNA. linc01614 was notably upregulated in PC tissues and cell lines and was associated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
(59 reference statements)
1
6
0
Order By: Relevance
“…Dysregulated phosphate metabolism enhances the osteoblast gene and promotes mineralization [ 48 ]. According to existing literature, LINC01614 can promote pancreatic cancer progression by WNT/β‑catenin signaling which is the crucial pathway in aortic valve calcification [ 49 ]. While expression of the WNT/β‑catenin signaling pathway can also be against phosphate-induced calcification [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated phosphate metabolism enhances the osteoblast gene and promotes mineralization [ 48 ]. According to existing literature, LINC01614 can promote pancreatic cancer progression by WNT/β‑catenin signaling which is the crucial pathway in aortic valve calcification [ 49 ]. While expression of the WNT/β‑catenin signaling pathway can also be against phosphate-induced calcification [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signaling pathway promotes tumor progression and metastasis in various types of cancer, such as gastric cancer, pancreatic cancer, lung cancer, and cervical cancer (24)(25)(26)(27)(28)(29). Previous studies have shown that the Wnt/β-catenin pathway is activated in numerous types of cancer, including cervical cancer (30-32).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting the original activity of lncRNAs by binding specific proteins is another way to regulate the Wnt/β-catenin pathway. Both lncRNA long intergenic non-protein coding RNA 01614 (LINC01614) [35] binding GSK-3β and lncRNA LINC01197 [36] binding β-catenin can affect the original function of the protein to regulate Wnt signal transduction.…”
Section: Lncrnas Regulate Wnt/β-catenin Signaling Pathway In Pcmentioning
confidence: 99%